The Influence of The Business Ecosystem and Customer Base On Increasing Third-Party Funds In The Region III Office - Diani Wahyu Setyanti (Publikasi Indonesia, 2024)
The purpose of this research to identify influence of the business ecosystem and customer base on increasing third-party funds in the region III office. Judging at the existing problem, the researcher applies a quantitative approach. The quantitative approach to business is research in the field of business with the aim of research through empirical assessment involving measurement and analysis of numbers. Quantitative research stands alone in the sense that it does not meet the needs of analytical interpretation. This research was conducted with the aim to see the influence of business ecosystem and customer base on Bank BTN's deposits. In addition, this study also aims to encourage an increase in deposits as well as to become the main target of Bank BTN. This study used multiple regression analysis method which was analyzed using the Eviews 10 application platform. As described in chapter IV, the conclusions of this study can be drawn as follows: Partially, the business ecosystem has a positive but significant effect on increasing Bank BTN's deposits. This means that when the business ecosystem rises, deposits will increase and vice versa. Meanwhile, the customer base has a positive and significant influence on the increase in deposits of Bank BTN. That is, when the customer base rises, DPK will also increase, and vice versa. Simultaneously, the business ecosystem and customer base together have a significant influence on Bank BTN's deposits.